Avian feathers as a non-destructive bio-monitoring tool of trace metals signatures: A case study from severely contaminated areas. (January 2015) - Abdullah, Muhammad; Fasola, Mauro; Muhammad, Ashiq; Malik, Salman Ahmad; Bostan, Nazish; Bokhari, Habib; Kamran, Muhammad Aqeel; Shafqat, Mustafa Nawaz; Alamdar, Ambreen; Khan, Mudassar; Ali, Nadeem; Eqani, Syed Ali Musstjab Akber Shah
Highlights: Trace metals were assessed in avian feathers collected from industrial areas. Concentrations among the highest ever found in similar samples were recorded. Such high concentrations of Cr, Pb, Cd may affect avian reproduction. Avian feathers are a convenient sampling tool for assessing metal contamination. Abstract: The concentrations of trace metals were assessed using feathers of cattle egrets ( Bubulcus ibis ), collected within two industrial areas of Pakistan, Lahore and Sialkot. We found, in order of descending concentration: Zinc (Zn), Iron (Fe), Nickel (Ni), Copper (Cu), Cadmium (Cd), and Manganese (Mn), Chromium (Cr), Arsenic (As), and Lithium (Li), without any significant difference (except Fe, Zn, and Ni) between the two areas. The concentrations of trace metals, we recorded were among the highest ever reported in the feathers of avian species worldwide. The concentrations of Cr, Pb, Cd were above the threshold that affects bird reproductive success. The high contamination by heavy metals in the two areas is due to anthropogenic activities as well to natural ones (for As and Fe). The bioaccumulation ratios in eggs and feathers of the cattle egret, their prey, and the sediments from their foraging habitats, confirmed that avian feathers are a convenient and non-destructive sampling tool for the metal contamination. The results of this study will contribute to the environmental management of the Lahore and Sialkot industrial areas.